Frequency and spectrum of M2 mutants and genetic variability in cyto-agronomic characteristics of fenugreek induced by caffeine and sodium azide - Naaz, Neha; Choudhary, Sana; Sharma, Nidhi; Hasan, Nazarul; Al Shaye, Najla A.; Abd El-Moneim, Diaa (Frontiers in Plant Science, 2023)
Trigonella foenum graecum L. (Fenugreek) is a valuable medicinal plant cultivated for decades for its therapeutic characteristics. Still, no pronounced improvement concerning wild form was accomplished as it is a self-pollinating crop. Induced mutagenesis is encouraged as a remarkable tool on this plant to circumvent the genetic bottleneck of cultivated germplasms. As a result, develop novel allelomorphic combinations for short-term agronomic attributes. Fenugreek cultivar PEB (Pusa Early Bunching), selected for the present experiment, was mutagenized with five doses (0.2%, 0.4%, 0.6%, 0.8%, and 1.0%) of caffeine and sodium azide (SA) to evaluate its impact on qualitative and quantitative traits of M1 and M2 generation conducted in a Complete Randomized Block Design (CRBD), replicated five times during 2019-20 and 2020-21 respectively. The frequency of induced phenotypic variations was assessed in M2 progenies, resulting in the identification and isolation of a broad spectrum of mutants with altered phenotypes. Mutagenic effectiveness and efficiency were found to be maximum at lower concentrations of the mutagen treatments, highest in SA, followed by caffeine. Various morphological mutants with modified characters were observed at different concentrations in M2 generation. The spectrum of mutations was wider in SA than in caffeine, as caffeine produced 51 while SA produced 54 individual mutants under seven major categories. The maximum frequency of morphological mutants was associated with leaf, followed by plant size, plant growth habit, pod, seed size, seed shape, and seed color. Morphological and structural variations in guard cells of stomata and seeds were observed through Scanning Electron Microscopy (SEM). The variations created in the economically important traits may enrich the genetic diversity of this plant species. Moreover, these morphological mutants may serve as a source of elite genes in further breeding programmes of fenugreek.